E-Learning Barriers and Solutions to Knowledge Management and Transfer - N.D, Oye; ., A.Iahad N. (Information Management and Business Review, 2011)
This paper present a systematic overview of barriers and solutions of e learning in knowledge management (KM) and knowledge transfer (KT) with more focus on organizations. The review paper also discusses KT in organizational settings and KT in the field of e learning. Here, an e-learning initiative shows adaptive solutions to overcome knowledge transfer barriers. The paper concludes that the flow of knowledge depends on people and the social environment they operate in. Therefore E-Learning environments support knowledge transfer not only by helping learners to make sense of content, but also by enabling communication, both among learners and between learners and tutors.